Reflexology for the VTCT Diploma - Cressy, Susan (Oxford : Heinemann, 2003)
This title covers the VTCT Diploma in Reflexology, and has a section on setting up a business.
Previous ed.: 2002.
Includes index.
Keywords: Reflexology (Therapy); Health and Fitness